Anion photoelectron spectroscopy of free [Au25(SC12H25)18]−. Issue 36 (1st September 2017) - Hirata, Keisuke; Yamashita, Keishiro; Muramatsu, Satoru; Takano, Shinjiro; Ohshimo, Keijiro; Azuma, Toshiyuki; Nakanishi, Ryuzo; Nagata, Takashi; Yamazoe, Seiji; Koyasu, Kiichirou; Tsukuda, Tatsuya
Abstract : The adiabatic electron affinity of [Au25 (SC12 H25 )18 ] 0 was experimentally determined to be 2.2 eV by anion photoelectron spectroscopy. Abstract : Previous theoretical studies have shown that the thiolated gold cluster compound [Au25 (SR)18 ] − can be viewed as a prototypical superatom with a closed electronic structure. The quantized electronic structure of [Au25 (SR)18 ] − has been experimentally demonstrated by optical and electrochemical methods in the dispersed state. Nevertheless, no direct information is available on the energy levels and densities of occupied states. Here, we report the photoelectron spectrum of [Au25 (SC12 H25 )18 ] − isolated under vacuum for the first time. The spectrum exhibits two distinct peaks, corresponding to electron detachment from the superatomic 1P orbitals and Au 5d orbitals of the Au13 core. The adiabatic electron affinity of [Au25 (SC12 H25 )18 ] 0 was experimentally determined to be 2.2 eV, which is significantly smaller than that of [Au25 (SCH3 )18 ] 0 predicted theoretically.